Sovereignty in Postcolonial Aotearoa New Zealand: Ambiguities, Paradoxes, and Possibilities. Issue 2 (28th October 2013) - Barrett, Jonathan; Strongman, Luke
Abstract : The Treaty of Waitangi, concluded between many Māori chiefs and the British Crown in 1840, is the foundational testament of Aotearoa New Zealand. Despite the constitutional character, its status, subject matter, and terms of the treaty are disputable. Legal positivists deny the validity of the treaty; the English text, but not the Māori version, supports cession of sovereignty despite the Māori probably not sharing the European conception of sovereignty. Such ambiguities and paradoxes obstruct categorical conclusions being drawn about sovereignty and the treaty. This article destabilizes and remystifies the positivist conception of Crown (state) sovereignty, rather than establishing illusory certainties about sovereignty in Aotearoa New Zealand. Stripped of its positivist certainties, sovereignty, on a day‐to‐day basis, may be seen to concern the ways self‐determining peoples protect, preserve, and develop their cultures. Viewed in this light, sovereignty in Aotearoa New Zealand cannot plausibly be claimed by one particular culture; therefore, other solutions must be considered.